FLIP TEACHING IN PROMOTING ACTIVE STUDENT LEARNING - B, Ligi; Dharma Raja, B. William (International Journal of Research -GRANTHAALAYAH, 2016)
During the past decade, the teachers in the schools have increased their use of Internet based content and resources in their classrooms. This paper briefly explains about a new teaching method known as flip teaching (FT) where students can adjust some features according to their preferences and learning style, which also supports to educate the children in a active learning(AL) environment. The system is capable of assisting children which can make them engage in learning activities successfully. This environment enables monitoring students’ progress, total time students have spent in the system, their activity on the class, the overall achievements in lessons learned, tests performed and solutions to given projects which helps in active student learning. Personalized assistance that teacher provides in a traditional classroom is not easy to implement. FT is booming as the education becomes more demand-focused. Also, this method suggests ways to bridge the gaps between students and instructors and students and their peers, which are typical of online learning and face-to-face learning.